Roadmap on electromagnetic metamaterials and metasurfaces - Cui, Tie Jun (2024)
The flourishing area of electromagnetic (EM) metamaterials and metasurfaces has attracted significant interests for several decades. Early work can be traced back to 1968 when Victor G. Veselago firstly presented the theory of negative refraction with negative permittivity and negative permeability [1]. Then in late 1990s, Sir John B. Pendry proposed a methodology to realize the negative permittivity [2] and negative permeability [3] using periodically-arranged metallic wires and split-ring resonators in subwavelength scale, establishing the fundamental theory and experimental research of metamaterials [4, 5]. In the early-stage researches, the effective medium theories play an important role in describing the macroscopic properties of three-dimensional EM metamaterials, and diversely novel physical phenomena have been demonstrated, including the negative refraction, perfect lens and superlens, and invisibility cloaking. Therefore, the metamaterials characterized by effective medium theories are also called as effective medium metamaterials. Although there is a long history of the effective medium metamaterials, there are still ongoing scientific breakthroughs and emerging engineering applications nowadays.